- If x = 5 is a zero of the given polynomial, then,
- (x - 5) is a factor of the polynomial. [Since, x = 5 or, x - 5 = 0]
- Now, divide the polynomial with (x - 5) using long division method. (See the picture)
- We get (x^2 - x - 6) as the quotient.
- Now, factorise the above polynomial:
- (x^2 - x - 6)
- = (x^2 - 3x + 2x - 6)
- = x(x - 3) + 2(x - 3)
- = (x - 3)(x + 2)
- Therefore, x^3 − 6x^2 − x + 30 = (x − 5)(x − 3)(x + 2)
Answer:
B.(x − 5)(x − 3)(x + 2)
Hope you could get an idea from here.
Doubt clarification - use comment section.